Topological Degree Method for Stochastic Pantograph Differential Equation with Hilfer Fractional Derivative Involving Non-instantaneous Impulses - Louakar, Ayoub; Vivek, Devaraj; Kajouni, Ahmed; Hilal, Khalid (Discontinuity, Nonlinearity, and Complexity, 2026)
This study examines a class of fractional stochastic pantograph differential equations involving the Hilfer fractional derivative and non-instantaneous impulses. The existence of solutions is established using topological degree theory, while Banach's contraction principle is employed to demonstrate uniqueness. Additionally, an illustrative example and graphical analysis are provided to validate the findings.